Serum TSH levels as a predictor of malignancy in thyroid nodules: A prospective study. - Lenara Golbert; Ana Patrícia de Cristo; Carlo Sasso Faccin; Mauricio Farenzena; Heloísa Folgierini; Marcia Silveira Graudenz; Ana Luiza Maia (PLoS ONE, 2017)
The role of serum TSH concentrations as a predictor of malignancy of thyroid nodule remains unclear.To prospectively evaluate the usefulness of serum TSH levels as a predictor of malignancy in thyroid nodules.Patients with thyroid nodule(s) who underwent fine-needle aspiration biopsy under ultrasonographic guidance in a tertiary, university-based hospital were consecutively evaluated. Patients with known thyroid cancer and/or patients receiving thyroid medication were excluded. Serum TSH levels were measured by two differents methodologies, chemiluminescent (CLIA) and electrochemiluminscent immunoassay (ECLIA). Anatomopathological exam of tissue samples obtained at thyroidectomy was considered the gold standard for the diagnosis of thyroid cancer.A total of 615 patients participated in the study. The mean age was 55.9±14.7 years, and 544(88.5%) were female. The median TSH values were 1.48 and 1.55 μU/mL, using CLIA and ECLIA, respectively. One-hundred-sixty patients underwent thyroidectomy and the final diagnoses were malignant in 47(29.4%) patients. TSH levels were higher in patients with malignant than in those with benign nodules in both TSH assays: 2.25 vs. 1.50; P = 0.04 (CLIA) and 2.33 vs. 1.27; P = 0.03 (ECLIA). Further analysis using binary logistic regression identified elevated TSH levels, a family history of thyroid cancer, the presence of microcalcifications, and solitary nodule on US as independent risk factors for malignancy in patients with thyroid nodules. Additional analyses using TSH levels as a categorical variable, defined by ROC curve analysis, showed that the risk of malignancy was approximately 3-fold higher in patients with TSH levels ≥2.26 μU/mL than in patients with lower TSH levels (P = 0.00).Higher serum TSH levels are associated with an increased risk of thyroid cancer in patients with thyroid nodules. Using TSH levels as an adjunctive diagnostic test for stratifying the risk of malignancy associated with a thyroid nodule may help on defining the best therapeutic approaches.